The influence of effective utilization degree of diesel engine cylinder air charge on soot emission and indicated efficiency - Matievsky, Dmitry; Svistula, Andrew (Transport, 2005)
Mathematical simulator results of the influence of effective utilization degree of (a diesel engine) cylinder air charge on soot emission and connected losses of heat are given in this paper. Increase reserve of the indicated efficiency by the reduction of inopportunity of soot burning and radiation heat exchange loss is shown.First Published Online: 27 Oct 2010